Mapping surface residues of eIF5A that are important for binding to the ribosome using alanine scanning mutagenesis - Barbosa, Natália M. [UNESP]; Boldrin, Paulo E. G. [UNESP]; Rossi, Danuza [UNESP]; Yamamoto, Priscila A. [UNESP]; Watanabe, Tatiana F. [UNESP]; Serrão, Vitor H.; Hershey, John W. B.; Fraser, Christopher S.; Valentini, Sandro R. [UNESP]; Zanelli, Cleslei F. [UNESP] (Springer Nature, 2016)
The translation elongation factor eIF5A is conserved through evolution and is necessary to rescue the ribosome during translation elongation of polyproline-containing proteins. Although the site of eIF5A binding to the ribosome is known, no systematic analysis has been performed so far to determine the important residues on the surface of eIF5A required for ribosome binding. In this study, we used clustered charged-to-alanine mutagenesis and structural modeling to address this question. We generated four new mutants of yeast eIF5A: tif51A-4, tif51A-6, tif51A-7 and tif51A-11, and complementation analysis revealed that tif51A-4 and tif51A-7 could not sustain cell growth in a strain lacking wild-type eIF5A. Moreover, the allele tif51A-4 also displayed negative dominance over wild-type eIF5A. Both in vivo GST-pulldowns and in vitro fluorescence anisotropy demonstrated that eIF5A from mutant tif51A-7 exhibited an importantly reduced affinity for the ribosome, implicating the charged residues in cluster 7 as determinant features on the eIF5A surface for contacting the ribosome. Notably, modified eIF5A from mutant tif51A-4, despite exhibiting the most severe growth phenotype, did not abolish ribosome interactions as with mutant tif51A-7. Taking into account the modeling eIF5A + 80S + P-tRNA complex, our data suggest that interactions of eIF5A with ribosomal protein L1 are more important to stabilize the interaction with the ribosome as a whole than the contacts with P-tRNA. Finally, the ability of eIF5A from tif51A-4 to bind to the ribosome while potentially blocking physical interaction with P-tRNA could explain its dominant negative phenotype.
Keywords: eIF5A; Hypusine; Ribosome binding; Translation elongation